2017
DOI: 10.1111/febs.14144
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated loss of FGF5 function increases wool staple length in sheep

Abstract: Fibroblast growth factor 5 (FGF5) regulates hair length in humans and a variety of other animals. To investigate whether FGF5 has similar effects in sheep, we used clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated 9 (Cas9) to generate loss-of-function mutations with the FGF5 gene in Chinese Merino sheep. A total of 16 lambs were identified with genetic mutations within the targeting locus: 13 lambs had biallelic modifications and three lambs had monoallelic modifications. Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 31 publications
0
26
0
4
Order By: Relevance
“…Consequently, we carried out a prediction of target genes and verified that FGF5 was a target gene of conserva-tive_NC_013672.1_9290 and conservative_NC_013675.1_10734 miRNAs. FGF5 serves as a crucial regulator in hair length 35,36 and influences the hair cycle by regulating the anagen-catagen transition 35,[37][38][39] . Our results indicated that conservative_NC_013672.1_9290 and conservative_NC_013675.1_10734 were candidate regulatory miRNAs in the hair cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we carried out a prediction of target genes and verified that FGF5 was a target gene of conserva-tive_NC_013672.1_9290 and conservative_NC_013675.1_10734 miRNAs. FGF5 serves as a crucial regulator in hair length 35,36 and influences the hair cycle by regulating the anagen-catagen transition 35,[37][38][39] . Our results indicated that conservative_NC_013672.1_9290 and conservative_NC_013675.1_10734 were candidate regulatory miRNAs in the hair cycle.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate potential function of genes identified in the selection signature analysis, we first focused on a gene within our top ranking admixed locus (in the direction of llama to alpaca), comprising a set of candidate genes for adaptive introgression and artificial selection (ANTXR2/PRDM8/FGF5/C4orf22; see the "Results" section) [99,100] and in particular on FGF5. Since functional variation at FGF5 (also known as the angora gene) is known to correlate with short-or longwool phenotypes in sheep and goat [101,102], we examined sequence differences in this gene in short and longwool alpaca. Six healthy 2 year-old longwool (Suri) alpacas (3:3) and shortwool (Huacaya) alpacas (3:3) were selected for mRNA and protein expression testing using the skin samples.…”
Section: Functional Analysis Of Target Genesmentioning
confidence: 99%
“…In sheep, CRISPR/Cas9 has been applied to disrupt the normal function of the FGF5 gene, resulting in 3/18 (16.6%) mutated founders that carried a disruption in FGF5 and showed increased wool length (Hu et al, 2017). Another publication has also reported the generation of FGF5 -disrupted sheep; 16/20 (80%) mutated founders carried both monoallelic and biallelic mutations in FGF5 and showed increased wool length and quantity (Li et al, 2017c). Recently, Zhang et al have also confirmed that the disruption of FGF5 in sheep can lead to an increased wool length and average wool growth rate (Zhang et al, 2019c).…”
Section: Applications Of Crispr/cas9 In Sheep and Goatsmentioning
confidence: 99%